Strengthening Character Education Based on Local Wisdom at SD Negeri Panaikang 3, Makassar City - Ahmad; Farhan Dwinanda Hanisyahputra; Nur Alim Bahri; Dedi Harianto; Ridwan Andi Mattoliang (Outline Publisher, 2025)
Character education serves as a crucial foundation for shaping young generations with integrity, particularly amidst the challenges of globalization. This community service initiative aims to strengthen the character of students at SD Negeri Panaikang 3 by leveraging the local wisdom of South Sulawesi. A participatory approach was implemented, engaging 27 second-grade students through socialization sessions, workshops, and practical actions (waste sorting). Evaluation results revealed that 87% of students demonstrated a good understanding of the material, while 13% showed adequate comprehension. This activity proves that local wisdom can serve as an effective medium for instilling values of environmental care, mutual cooperation, and responsibility.